Innovation in nursing led maternal and infant care: emerging trends and impact in Indian clinical setting - Shukal, Riya Patel; Matere, Kavita V.; Badduri, Phanindrareddy; Umar, Mohammed; Bakshi, Pooja; R., Selvi; Shanmugam, Yamunadevi; Baby, Dana; P. F., Regina; Roslin, Anne; Suhashini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Nursing-led models of maternal and infant care are increasingly recognised as pivotal strategies for improving survival, quality of care, and patient experience in India’s evolving health system. Despite substantial gains in institutional delivery and service coverage, preventable maternal and neonatal deaths persist, largely due to gaps in quality, continuity and respectful care. This systematic review synthesises evidence on nursing- and midwifery-led innovations across community, facility, digital and quality-improvement domains in Indian clinical settings. Evidence indicates that community-based interventions such as home-based newborn care (HBNC), delivered through trained and supervised nursing cadres, significantly reduce neonatal mortality and improve early breastfeeding and care-seeking behaviours. Facility-based midwifery-led care, including midwifery-led care units (MLCUs), demonstrates lower intervention rates, enhanced maternal autonomy and high satisfaction without compromising neonatal outcomes among low-risk women. In neonatal intensive care units (NICUs), nurse-led developmental supportive care, Kangaroo mother care (KMC), breastfeeding counselling and maternal participation interventions improve neurobehavioural outcomes, thermoregulation, bonding and maternal mental wellbeing. Digital health innovations implemented by nurses, auxiliary nurse midwives (ANMs) and accredited social health activists (ASHAs) enhance health communication, tracking and service utilisation, while quality-improvement initiatives such as LaQshya strengthen intrapartum safety, teamwork and adherence to evidence-based practices. Key enablers include competency-based education, regulatory recognition of advanced nursing roles, supportive supervision, adequate staffing and integrated digital systems. Persistent fragmentation across the continuum of care remains a challenge, underscoring the need for integrated pathways linking community, labour room, postnatal and neonatal services.